In-situ Field Gamma Spectrometry in a Radionuclide Air Sampler. Issue 4 (8th October 2022) - Lebel, Luke; Barlow, Kyle; Boulianne, Diana; Clouthier, Tony
Abstract: The work being presented is on the development of a system to measure the speciation of airborne radionuclide emissions from the environment during a nuclear emergency. On-site air sampling measurements that were conducted during the Fukushima Daiichi accident were limited because field teams had to be sent out to run the sampling systems and retrieve the filters for gamma spectrometry analysis in a separate laboratory. The start of air sampling was delayed, and it was impossible for emergency responders to use the information about the airborne radionuclide composition in a timely way. The goal of the current study is to develop a system that could provide live, near real-time information about the concentrations of different radionuclides in the air without having to rely on human intervention. The development of the prototype in the current work is largely being enabled by Cd-Zn-Te spectrometers, which provide reasonably high-resolution spectrometry given that it is a room temperature sensor, and allow the measurements to be conducted in the field. A custom filter cartridge has been designed to hold a pair of aerosol and iodine filters in place while keeping the gamma spectrometers as close as possible in order to obtain high count rate efficiencies. A single cartridge holds both filters and has an internal flow channel directing the air flow between them. The cartridge design also facilitates replacing the filters as the accumulated radioactivity on the filters becomes too high. An automation system can move a filter cartridge from the fresh cartridge storage bank to the sampling location (filtration and gamma spectrometry) and return the used filter cartridge to the used cartridge storage bank. The radionuclide air sampling system prototype has been designed and constructed. It has been tested with fixed sources located on the respective aerosol and iodine filters. The real-time data capture aspects of the system were also demonstrated with a live 131 I capture experiment. The projected performance of the system during a reactor accident was also simulated, emulating the characteristic detector efficiencies and projecting how the airborne concentrations could be reconstructed. The study has designed and constructed a radionuclide air sampler that could be used for measuring airborne radioactivity in emissions from a nuclear accident. Because the gamma spectrometry measurements are done in situ with good resolution and the system is automated, it would allow data to be transmitted back to an emergency operations center immediately rather than having to wait for additional laboratory analysis.